Pilot study of a paediatric emergency department oral rehydration protocol. Issue 2 (20th January 2005) - Boyd, R; Busuttil, M; Stuart, P
Abstract : Objective: To ascertain if the use of a paediatric oral rehydration protocol in the emergency department changed rates of admission, total time spent in hospital, total time spent in the emergency department, or number of unscheduled returns to the emergency department. Methods: A two month time period was analysed before and then after the adoption of an oral rehydration protocol for children presenting to the emergency department with symptoms suggestive of gastroenteritis. The rates of admission, total time spent in hospital, total time spent in the emergency department, and the rate of unscheduled returns were analysed using Fisher's exact and Wilcoxon testing for non-parametric data. Results: The adoption of a paediatric rehydration protocol was associated with a significant reduction in admission rates (before = 22.5%, after 5.1%; p = 0.048) and mean total hospital time (before = 7 hours 54 minutes, after = 2 hours 17 minutes; p = 0.017). There was no significant difference in time spent in the emergency department (before = 1 hour 25 minutes, after 1 hour 35 minutes, p = 0.3). The number of unscheduled returns did not change significantly (p = 0.3). Conclusion: Adoption of a paediatric rehydration protocol significantly reduces admission rates and total time spent in hospital for children presenting to the emergency department with symptoms of gastroenteritis. The mean time spent in the actual emergency department does not significantly increase. The rate of unscheduled returns does not change.